The relationship between obliteration of coronal, sagittal, and lambdoid cranial sutures (ectocranial-endocranial) and biological age: a meta-analysis - Satriyo, Juanda; Soedarsono, Nurtami; Auerkari, Elza Ibrahim; Gultom, Ferry Pergamus (Universitas Padjadjaran, 2025)
Introduction: Age estimation using ectocranial and endocranial cranial sutures is an important technique in forensic science and forensic odontology. This meta-analysis aims to evaluate the relationship, accuracy, and reliability of this method by reviewing findings from previously published studies. Methods: A systematic search was conducted on electronic databases including PubMed, Scopus, and Web of Science to identify relevant research published between 2019 and 2024. Inclusion criteria encompassed original studies that applied cranial suture methods for age estimation on adult human cranial bone samples. Out of 23 identified articles, 7 met the criteria and were included in the quantitative analysis. Results: A moderate to strong positive correlation between the biological age of adults and the closure score of cranial sutures (coronal, sagittal, and lambdoid) both ectocranially and endocranially (r=0.58) with a 95% confidence interval [0.2928,0.7750]. Factors affecting accuracy include population variation, types of sutures evaluated, and scoring methods. Conclusion: This meta-analysis confirms that the cranial suture method has limited utility in forensic age estimation. Nevertheless, this technique can still provide additional information when used in conjunction with other skeletal and dental indicators. Standardization of methodology and further research are needed to improve the accuracy of cranial suture-based age estimation.